The Chemical Composition of Packaged Drinking Water: Inorganic and Organic Contaminants, Disinfection Byproducts, and Microplastics - Suriani Nur (Science Journal Get Press, 2025)
This research explores the chemical constituents of bottled drinking water, emphasizing the presence of inorganic and organic pollutants, microplastics, and disinfection byproducts. Samples from five top-selling PET-bottled water brands were analyzed in triplicate under different storage temperatures (room temperature, 4°C, and 40°C). Various analytical techniques were employed: Atomic Absorption Spectroscopy (AAS) to quantify heavy metals (Pb, Cd, Sb), Gas Chromatography–Mass Spectrometry (GC-MS) to detect bisphenol A (BPA) and phthalates, Fourier Transform Infrared Spectroscopy (FTIR) for microplastic identification, and High-Performance Liquid Chromatography (HPLC) to assess trihalomethanes (THMs). Antimony (Sb) was consistently detected, with concentrations increasing markedly at elevated temperatures. BPA appeared in 60% of samples and showed a temperature-dependent increase and inverse correlation with pH. All samples contained microplastics (mean 22 ± 8 particles/L), primarily PET, polypropylene (PP), and polyethylene (PE). Although all contaminant levels were within regulatory thresholds, repeated intake under suboptimal storage conditions may raise cumulative exposure. The results emphasize the need for stricter regulatory measures, enhanced labeling for storage, and standardized guidelines concerning microplastics. This study enhances current understanding by demonstrating how storage conditions influence chemical leaching and potential health risks linked to long-term bottled water consumption.